(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current study, which was conducted at the Plant pathology laboratory, Rama University in Kanpur (2020), examined the effects of varying concentrations of fungicides, botanical and biocontrol agents on radcal growth and per cent inhibition of Fusarium oxysporum f. sp. ciceris in vitro.